Mixing state of printer generated ultrafine particles: Implications for the complexity of indoor aerosols. (15th August 2021) - Wang, Hao; He, Congrong; Modini, Rob L.; Wang, Wenlu; Lu, Haoxian; Morawska, Lidia
Abstract: The operation of laser printers can lead to the emission of high numbers of ultrafine particles. Evidence on the toxicology and adverse health effects of these particles has been mounting, however few studies have investigated the complexity of these particles in terms of their volatility, hygroscopicity and mixing state. This study utilized a Volatility Hygroscopic Tandem Differential Mobility Analyzer (VH-TDMA) to explore the internal and external mixing states of printer-generated particles. Up to 6.0 × 10 5 particles. cm −3 were observed during the operation of the laser printer, and these ultrafine particles could be classified into three groups, each with its own particular volatility (i.e., gradually shrinkable, suddenly shrinkable and expandable), owing to the different internal mixing states. In particular, we propose shell-core structures to explain the special volatility of these particles. In addition, whilst the majority of the generated particles were initially hydrophobic at 90% relative humidity (RH), it was observed that there were a very small number of volatilized particles (less than 5%) that shrank (i.e., decreased in size) after humidification. This study can be used as a model for investigating the complex particle formation processes in relation to secondary organic aerosols from other sources. Furthermore, our results shed light on the complexity of indoor aerosols, which should be investigated further in future indoor air quality studies. Graphical abstract: Image 1 Highlight: Mixing state of printer-generated particles was measured for the first time. Three different types of particles were identified in the printer emissions. Physical models were developed for particle formation and ageing under different printing scenarios.